PERBANDINGAN LAMA RAWAT INAP PASIEN PNEUMOTORAKS SPONTAN PRIMER DENGAN TATA LAKSANA CHEST TUBE DRAINAGE (CTD) DAN NEEDLE ASPIRATION (NA): META-ANALYSIS - Rahmad Teguh Ananda Pandia (2022)
Pneumothorax is a condition that must be treated immediately after diagnosis. The most common treatment option used by Primary Spontaneous Pneumothorax (PSP) patients was Chest Tube Drainage (CTD) and Needle Aspiration (NA). Based on previous research, it was found that the two treatments did not have a significant difference in the rate of immediate success, recurrence for one year, recurrence for one week, recurrence for three weeks or complications. Therefore, the researchers conducted a meta-analysis of the length of hospitalization to determine the differences between the two treatment methods. This research uses several studies obtained through PubMed and Science Direct databases, then analyzed using Revman 5.4.1. The results showed that all studies analyzed with a total of 573 patients showed that NA had a shorter length of stay with a mean difference of -2.10 [95% confidence interval (CI) -2.69 to -1.50] compared to CTD using a random effect model. There is a significant relationship between CTD and NA treatment in PSP patients with length of stay with a P value < 0.00001 with a difference in the mean of patients treated with NA in PSP patients with CTD management, the hospitalization was significantly reduced 2.10 times shorter.